Mapping clinical pharmacy practice in Swiss hospitals: a cross-sectional study. Issue 6 (26th February 2016) - Messerli, Markus; Maes, Karen A; Hersberger, Kurt E; Lampert, Markus L
Abstract : Background: Clinical pharmacy activities developed significantly in the last decade. The extent and organisation of these activities in Switzerland remained unknown. Objectives: To map clinical pharmacy services (CPS) provided in Swiss hospitals and to discuss their development focusing on different cultural regions and healthcare systems. Methods: We enrolled all chief hospital pharmacists affiliated with the Swiss Society of Public Health Administration and Hospital Pharmacists (n=47) for an online survey. We asked them to describe the extent and organisation of CPS concerning patient-related, therapy-related or process-related activities, the structural organisation and the available human resources. Results: The survey took place from March to April 2013. It was completed by 44 chief hospital pharmacists (return rate 94%), representing the hospital landscape in Switzerland comprehensively. Thirty-three (75%) hospitals offered regular CPS and seven (16%) planned to do so. Institutions in regions without drug-dispensing physicians rather employed pharmacists assigned with clinical activities (n=20, 22% of 135.3 full-time equivalent (FTE)) than regions with partial (n=8, 7% of 35.8 FTE) or unrestricted drug dispensing by physicians (n=16, 6% of 68.1 FTE, p=0.026). Of hospitals with implemented CPS, 73% had weekly interprofessional ward rounds, and in 9.1%, clinical pharmacists daily reconciled medicines at patient discharge. Conclusions: Our data show regional differences in the implementation and pattern of CPS. A significant correlation to drug dispensing by physicians in ambulatory care and human resources provided for CPS was found. While interprofessional ward rounds were performed periodically, seamless care activities by clinical pharmacists remained insufficiently established.